1, 4‐Dioxane Soil Remediation Using Enhanced Soil Vapor Extraction (XSVE): II. Modeling. Issue 2 (31st March 2018) - Burris, David R.; Johnson, Paul C.; Hinchee, Robert E.; Dahlen, Paul R.
Abstract: 1, 4‐Dioxane is a volatile organic compound that is fully miscible in water, allowing it to sequester in vadose zone pore water and serve as a long‐term source of groundwater contamination. Conventional soil vapor extraction (SVE) removes 1, 4‐dioxane; however, substantial 1, 4‐dioxane can remain even after other colocated chlorinated solvents have been remediated. A field demonstration of "enhanced SVE" (XSVE) with focused extraction and heated injection was conducted at former McClellan AFB, CA, achieving 94% reduction in soil concentrations. A screening‐level tool, HypeVent XSVE, was created to assist in system design and data reduction and to anticipate how operating factors affect XSVE performance (e.g., cleanup level, remediation time, etc.). It assumes well‐mixed conditions, and combines an energy balance, mass balances for water and contaminant, and a temperature‐dependent 1, 4‐dioxane Henry's Law constant. User inputs include the target treatment zone size, initial 1, 4‐dioxane and soil moisture concentrations, and ambient site and injection/extraction conditions (temperature, humidity). Projections based on inputs representative of demonstration site conditions adequately anticipated the observed macroscopic field results. Sensitivity analyses show that removal increases with increasing heated air injection temperature and relative humidity and decreasing initial soil moisture content.